2020
DOI: 10.6004/jnccn.2020.0047
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Myeloid Leukemia, Version 2.2021, NCCN Clinical Practice Guidelines in Oncology

Abstract: Chronic myeloid leukemia (CML) is defined by the presence of Philadelphia chromosome (Ph) which results from a reciprocal translocation between chromosomes 9 and 22 [t(9;22] that gives rise to a BCR-ABL1 fusion gene. CML occurs in 3 different phases (chronic, accelerated, and blast phase) and is usually diagnosed in the chronic phase. Tyrosine kinase inhibitor therapy is a highly effective first-line treatment option for all patients with newly diagnosed chronic phase CML. This manuscript discusses the recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
228
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(233 citation statements)
references
References 268 publications
(370 reference statements)
2
228
0
3
Order By: Relevance
“…Guidelines also suggest proper follow-up includes frequent molecular monitoring, with monthly visits for the first six months and then every three months thereafter. In general, though, the reference criteria in TKI discontinuation eligibility outside of a clinical trial are quite strict as shown by both the ESMO and the very recently updated NCCN guidelines (17). A shared recommendation is to exclude patients with high Sokal risk or with a previous history of accelerated phase or blast phase CML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines also suggest proper follow-up includes frequent molecular monitoring, with monthly visits for the first six months and then every three months thereafter. In general, though, the reference criteria in TKI discontinuation eligibility outside of a clinical trial are quite strict as shown by both the ESMO and the very recently updated NCCN guidelines (17). A shared recommendation is to exclude patients with high Sokal risk or with a previous history of accelerated phase or blast phase CML.…”
Section: Discussionmentioning
confidence: 99%
“…However, because data available on treatment-free remission (TFR) are only for patients in the chronic phase and not for CML in advanced phases, current clinical guidelines and recommendations suggest TFR for chronic-phase patients only (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BM-MNCs of 30 healthy donors were used as normal controls (NC). Chronic myeloid leukemia was diagnosed by molecular biology, bone marrow morphology, immunology, and cytogenetics examination (19,20). Patients with severe cardiopulmonary, renal or liver failure or coagulation abnormality or pregnant were excluded.…”
Section: Specimen Collectionmentioning
confidence: 99%
“…Indeed, several current CML guidelines advocate the use of a sustained DMR, for at least 2 years, to select patients for consideration of TKI cessation. 10 , 11 …”
Section: Clinically Validated Tests For Detecting and Monitoring Bcr-abl1 And Kit Mutationsmentioning
confidence: 99%